Large bipolaron density at organic semiconductor/electrode interfaces. Issue 1 (December 2017) - Dhanker, Rijul; Gray, Christopher; Mukhopadhyay, Sukrit; Nunez, Sean; Cheng, Chiao-Yu; Sokolov, Anatoliy; Giebink, Noel
Abstract Bipolaron states, in which two electrons or two holes occupy a single molecule or conjugated polymer segment, are typically considered to be negligible in organic semiconductor devices due to Coulomb repulsion between the two charges. Here we use charge modulation spectroscopy to reveal a bipolaron sheet density >1010 cm−2 at the interface between an indium tin oxide anode and the common small molecule organic semiconductorN, N ′-Bis(3-methylphenyl)-N, N ′-diphenylbenzidine. We find that the magnetocurrent response of hole-only devices correlates closely with changes in the bipolaron concentration, supporting the bipolaron model of unipolar organic magnetoresistance and suggesting that it may be more of an interface than a bulk phenomenon. These results are understood on the basis of a quantitative interface energy level alignment model, which indicates that bipolarons are generally expected to be significant near contacts in the Fermi level pinning regime and thus may be more prevalent in organic electronic devices than previously thought. Bipolarons - two electrons or holes localized on the same molecule - are generally considered negligible in organic electronic devices. Dhanker et al. show that large bipolaron densities can exist near electrode interfaces and that they are linked to the phenomenon of unipolar organic magnetoresistance.